'Continuity and change', large‐scale assessment and equity: a study of gender‐related differences regarding conceptual knowledge. Issue 2 (15th October 2020) - Rosenlund, David
Abstract : The study examines how students in Grade 9 handle conceptual knowledge through the concept of continuity and change in the context of large‐scale assessment. The research questions address (a) what strategies the students use when they use the two parts of the concept concomitantly and (b) any gender‐related differences regarding these strategies. A total of 100 student responses on a specific item in the national test in history are examined. The method of concept analysis is applied to identify the strategies of the students from the two groups. The analytical framework is based on previous research regarding the concept. The results show that just over half of the students use the concept as expected. Boys are overrepresented among the students that struggle with the concept. Any correlation between the identified strategies is discussed in addition to the implications the results may have on equity and education.